2014
DOI: 10.1073/pnas.1407083111
|View full text |Cite
|
Sign up to set email alerts
|

Chaos–order transition in foraging behavior of ants

Abstract: The study of the foraging behavior of group animals (especially ants) is of practical ecological importance, but it also contributes to the development of widely applicable optimization problem-solving techniques. Biologists have discovered that single ants exhibit lowdimensional deterministic-chaotic activities. However, the influences of the nest, ants' physical abilities, and ants' knowledge (or experience) on foraging behavior have received relatively little attention in studies of the collective behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 24 publications
(34 reference statements)
1
58
0
2
Order By: Relevance
“…Considering these results, it becomes clear that the optimization [536][537][538][539] of the subsidy policy is indeed a difficult yet very important issue, which can mean the difference between a successful and an unsuccessful vaccination campaign. For the optimal outcome, it is important to carefully consider the mechanisms of individual decision-making, as well as to actually test on a representative sample how people respond to different external incentives in realistic situations.…”
Section: External Incentive Programsmentioning
confidence: 99%
“…Considering these results, it becomes clear that the optimization [536][537][538][539] of the subsidy policy is indeed a difficult yet very important issue, which can mean the difference between a successful and an unsuccessful vaccination campaign. For the optimal outcome, it is important to carefully consider the mechanisms of individual decision-making, as well as to actually test on a representative sample how people respond to different external incentives in realistic situations.…”
Section: External Incentive Programsmentioning
confidence: 99%
“…In the present study, our finding that older, postreproductively aged resident killer whale females lead group movement clearly demonstrates the potential of collective cognition to shape the evolution of life-history traits, such as menopause. The wisdom benefits of age are likely to be widespread and recent research has shown that older individuals in a range of taxa can improve the ability of groups to navigate, solve problems, and respond to potential dangers [17,18,35,36]. For instance, the reproductive success of elephants (Loxodonta africana) is enhanced in the presence of older female relatives, who are more capable of assessing social and predatory threats [17,36].…”
Section: If Many Animals Share Experience Gained With Age Why Is Menmentioning
confidence: 99%
“…For example, cellular automation-based models 34 can simulate one-dimensional unidirectional pheromone flow in an ant trail by controlling nonmonotonic variation of speed with the trail density and apply to a 2D robotic trail simulation for pedestrians, 35 and then study the spatio-temporal organization of ants on the trail to build bidirectional trails for other traffic systems. 4 In addition, researchers have developed mathematical models to analyze biological mechanisms or motion rules of ants 36,37 and provide a physics-based model for repulsively interacting self-propelled particles undergoing single-file motion. 38 However, directly applying the motion rules derived from the above data analyses often fails to produce realistic visual simulation of ants for CG applications, due to the intrinsic simplicity of the derived rules.…”
Section: Related Workmentioning
confidence: 99%